Implementasi Media Complete the Sentence terhadap Kemampuan Membaca dan Motivasi Belajar Kelas 3 SDN 16 Bireuen: The Implementation of Complete the Sentence Media on Reading Ability and Learning Motivation of Grade 3 Students at SDN 16 Bireuen - Supiati Supiati; Alfi Syahrin; Yulia Santi (ITScience (Information Technology and Science), 2026)
Reading proficiency is a crucial foundation for literacy among elementary school students. However, some students in lower grades still struggle to comprehend simple texts due to limited reading skills and low learning motivation. The